The effect of the make a match model on critical thinking skills and student motivation in reproductive system material - Aisyah, Nadin Rahma Nur; Kurniawati, Atik (Universitas Negeri Yogyakarta, 2026)
The critical thinking skills and motivation to learn of grade XI students at State High School in Yogyakarta need improvement, as 21st-century biology learning requires students to develop these skills. Therefore, Critical Thinking Skills can be achieved by applying appropriate learning models. The purpose of this study is to determine the effect of applying the Make a Match learning model on the Critical Thinking Skills and learning motivation of high school grade XI students in the material on the human reproductive system. The research design was a quasi-experimental study using a Non-Equivalent Pretest Posttest Control Group Design. The research was conducted at a State High School in Yogyakarta, involving all grade XI science students. The research sample was determined through purposive sampling, with class XI Science 2 as the experimental class and class XI Science 5 as the control class. The data collection technique in this study uses observation, tests, and the distribution of questionnaires. The data analysis technique used a nonparametric statistical analysis. The results showed that the Make a Match learning model had an effect on critical thinking skills and students’ learning motivation in the experimental class, with a significance value of 0.001 (p 0.05). The results of this study can serve as an innovative alternative learning strategy in biology to improve critical thinking skills and students’ motivation to learn. The application of this model encourages active engagement, social interaction, and collaborative concept analysis processes.